Psychosocial Risk and Work Stress in Logistics and Distribution - Lara-Calle, Andrés (2023)
The research is focused on studying the psychosocial risk factors and work stress in the logistics and distribution personnel of a company in the city of Latacunga, Ecuador. It contributes to the thematic area of the Psychology of Engineering, and the methodology follows a quantitative approach with a cross-sectional design and correlational scope. For data collection, the evaluation method of psychosocial factors designed by the National Institute of Safety and Health at Work of Spain through the FPSICO 4.0 software and the Work Stress Questionnaire developed by the World Health Organization are used. The study is conducted on 25 workers. The results show a 70% presence of psychosocial risk with a moderate to a high level, and there is low work stress of 68%. To identify if there is a possible relationship between psychosocial risk and work stress, the variables are analyzed. Initially, the Shapiro-Wilk normality test is performed, obtaining values less than 0.05, and there is no homogeneity between variables. Therefore, the non-parametric statistical test of Spearman’s correlation is established, in which a value of 0.38 is obtained, accepting the alternative hypothesis with a low correlation between the variables. In this sense, this demonstrates the importance of evaluating the work environment to identify the existence of risks that may be affecting the performance of workers and the fulfillment of business objectives. Finally, these results allow for creating awareness in the country to reduce or mitigate the existing risks and prioritize the health of workers.